Perancangan Jaringan Sistem Smart Home berbasis IoT menggunakan Cisco Packet Tracer dengan Metode Waterfall - Putra, Aditya Pratama; Darwis, Muhammad (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2025)
The development of information and communication technology has provided innovation in home automation, creating a smart home system that can provide comfort for its occupants. This study aims to design and test an IoT-based smart home system by implementing the development of the waterfall method using the cisco packet tracer platform. The designed system includes several IoT devices such as garage doors, lights, air conditioners, fans, sirens, surveillance cameras, doors, windows connected via an IoT server, wireless router, switch then controlled via a laptop and smartphone. The sensor functions to regulate light, temperature, to monitoring the home area from strangers, then will activate the actuator automatically. The steps in the waterfall approach begin with needs analysis, system design, implementation, and testing. The results of the simulation show that the system reacts to input from the sensor directly and executes commands as desired. Thus, this design can be a bridge to facilitate the development of a simple smart home system that is efficient and easy to apply